The Role of Essential Oils on Improving Elderly Skin Hydration - Linda Julianti Wijayadi; Kelvin Kelvin (Institute of Computer Science (IOCS), 2022)
Skin hydration has an important role in various diseases of the elderly. Skin hydration is determined by two factors, namely the ability of the stratum corneum (SC) to retain water due to natural moisturizing factors and the barrier function of the intercellular lipid lamellar structure and tight junctions. Several parameters are usually used for skin hydration, such as surface water content (SWC) and trans-epidermal water loss (TEWL). With age, several changes in the skin affect hydration, including changes in the cellular and intercellular lipid matrix, skin pH, SC protease enzymes, decreased sebaceous and sweat gland activity, and decreased estrogen levels in women. Therefore, a moisturizer is needed to minimize the unwanted effects of some of these changes. Selection of the type of moisturizer is very important for the elderly, especially moisturizers with antiseptic, antibacterial, and antioxidant effects are highly recommended. The ability of essential oils as components of moisturizers has been proven in various studies. Essential oils can improve the function of the epidermal barrier and help prevent transepidermal water loss. Therefore, this literature review discusses the role of various essential oils, namely green tea oils (Camellia sinensis or Camellia assamica), virgin coconut oils (Cocos nucifera L.), evening primrose oils (Oenothera paradoxa), grape seed oils (Vitis vinifera L.) .), rosemary oils (Rosmarinus officinalis L.), immortelle oils (Helichrysum italicum), and cannabis seeds oils (Cannabis sativa L.) on improving skin hydration in the elderly.